2014
DOI: 10.2139/ssrn.2463243
|View full text |Cite
|
Sign up to set email alerts
|

Parental Leave Benefits and Breastfeeding in Germany: Effects of the 2007 Reform

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…For example, there is ample evidence that universal healthcare coverage increases access to healthcare services, including immunization (41)(42)(43). Similarly, the presence of public or organizational policies providing women with paid maternity leave has been found to increase breastfeeding initiation and duration (44)(45)(46). Policies that ensure access to health insurance that covers immunization have also been found to determine access to immunization services, therefore, playing a signi cant role in immunization decision-making (42,47,48).…”
Section: Policy-level Factorsmentioning
confidence: 99%
“…For example, there is ample evidence that universal healthcare coverage increases access to healthcare services, including immunization (41)(42)(43). Similarly, the presence of public or organizational policies providing women with paid maternity leave has been found to increase breastfeeding initiation and duration (44)(45)(46). Policies that ensure access to health insurance that covers immunization have also been found to determine access to immunization services, therefore, playing a signi cant role in immunization decision-making (42,47,48).…”
Section: Policy-level Factorsmentioning
confidence: 99%
“…Our present study showed that maternal district of residence had no significant influence on EBF. By contrast, studies conducted in Bangladesh [9], Germany [25], and Tanzania [26] reported a significant influence of geographical location on EBF practice.…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, a study that investigated the paid parental leave (PPL) in Australia, drawing a sample from 2 prevalence surveys, observed better physical and mental health and well-being, in mothers during the post-PPL era, although the "effects were small" [27]. Another study that investigated the effects of Germany's Elterngeld (new parental leave benefits) 2007 policy on breastfeeding practices in Germany found that breastfeeding duration increased by 9.2% at 4 months and 7.9% at 6 months of infant age, respectively, among the beneficiaries of the parental leave reforms [25]. A systematic review of the literature with participants from Australia, Canada, Lebanon, Norway, Sweden, and the USA concluded that PML has health benefits, with longer paid leaves conferring higher impact [28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a range of studies from high-income countries, researchers have found that extending the duration of paid leave increases rates of breastfeeding for at least the critical first six months of the infant’s life [ 10 13 ]. Following reforms to Canada’s maternal (maternity plus parental) leave policy, which increased from 6 months to nearly 1 year in most provinces in 2000 [ 14 ], the share of women breastfeeding exclusively for at least 6 months increased by between 7.7 and 9.1 percentage points, according to a study that used longitudinal survey data to examine changes in health practices before and after the policy change [ 10 ].…”
Section: Paid Parental Leavementioning
confidence: 99%